Rhetorical syllogism in the English and the German language of automobile advertising - Jaganathan, Paramaswari; Siti Waltraud Mayr,; Nagaratnam, Florence Kannu (Penerbit UKM, 2014)
The language of advertising has a powerful impact on the branding of automobiles and sustaining its customer‟s loyalty. This study aims to identify the arguments used in advertisements; particularly on its claims, warrants and data to influence the automobile buyers in a diverse international market. It analyses the rhetorical devices and language equivalence used in the English and German print advertisements. A contrastive analysis of three cars‟ print advertisements, namely Mercedes Benz, BMW and Volkswagen from the German and Malaysian English dailies was carried out using Toulmin‟s model to identify the arguments and the rhetorical devices used in the advertisements. The study reveals two main similarities, particularly in the arguments put forth as well as the stylistic approach of the advertisements. The BMW and Mercedes Benz focused on their technological superiority and advancements, while the Volkswagen focused on its affordability. The German adverts were more persuasive and directed the buyers for action compared to the English adverts that provided more data and warrants. The BMW adverts also utilised a closed form compound adjectives such as “ConnectedDrive” to sustain the “hybrid concept” stylistic in line with the contemporary automobile advancement that focuses on hybrid cars. The use of figurative language was more prevalent in the English adverts compared to the German adverts to portray its internationalisation status of the car. These elements contribute to the pedagogical implications of teaching and learning foreign language; particularly for diverse writing purposes as well as planning business language for the different genres.